2016
DOI: 10.1002/jmv.24540
|View full text |Cite
|
Sign up to set email alerts
|

Incident and long-term HIV-1 infection among pregnant women in Brazil: Transmitted drug resistance and mother-to-child transmission

Abstract: Primary infection, seroconversion, and transmitted drug resistance (TDR) during pregnancy may influence the risk of mother-to-child-transmission (MTCT) of HIV-1 infection. This study estimated recent seroconversion, TDR rates, HIV-1 subtypes and pregnancy outcomes among 95 recently diagnosed, antiretroviral (ARV)-naïve pregnant women recruited during antenatal care in central western Brazil. Recent seroconversion was defined by BED-capture enzyme immunoassay (<155 days) and ambiguous nucleotides base calls (<1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Our studies have shown a significant percentage of recombinant BF1 forms (3.7–25.9%) in the Central West, North and Northeast Brazilian regions [11,2737]. The most recently described Brazilian CRFs_BF1 (CRF70_BF1 and CRF71_BF1) were identified among blood donors from Pernambuco State, Northeast region [22].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Our studies have shown a significant percentage of recombinant BF1 forms (3.7–25.9%) in the Central West, North and Northeast Brazilian regions [11,2737]. The most recently described Brazilian CRFs_BF1 (CRF70_BF1 and CRF71_BF1) were identified among blood donors from Pernambuco State, Northeast region [22].…”
Section: Discussionmentioning
confidence: 95%
“…The importance of BF1 recombinants in Brazil is further corroborated by the description of countless URFs in all country regions [2326]. Previous studies from our research group in different study populations in Central West, North and Northeast Brazilian States showed variable prevalence of BF1 recombinants in the pol subgenomic fragment: (Goiás: 3.7–18.1%, Mato Grosso: 11.9%, Mato Grosso do Sul: 8.2–25.9%, Tocantins: 7.7%, Maranhão: 7.5%, Piauí: 4.5% [11,2737]. …”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Mother-to-child transmission (MTCT) is the primary mode of HIV infection in children either during pregnancy, labor, and delivery or through breast feeding [46]. Several studies have proven that antiretroviral drugs decrease HIV transmission from the mother to the baby [7–11]. Particularly, the use of triple antiretroviral (ART) therapy during pregnancy has been proven to be highly effective in reducing mother-to-child HIV transmission from 15% up to 45% with no treatment at all to below 5% [12].…”
Section: Introductionmentioning
confidence: 99%